Distance career intervention with Portuguese higher education students: programme overview - Seabra, Filipa (2022)
The labour market has been facing significant changes over the last few years, fostered not only by technological advances but also by more competitive markets and new communication and interaction models within organizations and in the global society. Such trends are the basis for job perspectives that are becoming more flexible, but also less defined, insecure and unpredictable. From a future perspective, employable graduates will be those who are able to integrate scientific subject knowledge with transversal and career competencies, acting as agents in shaping their careers. This issue raises awareness of the graduates’ need to continuously learn and develop personal resources to facilitate their labour market integration and empower them for eventual job transitions. This paper aims to present a new distance intervention programme that seeks to promote the enrichment of the career resources of Higher Education (HE) students with different individual and socio-cultural characteristics, giving them the opportunity to engage in a development experience that can be valuable during HE studies and may have a positive impact afterwards, to meet the challenges of assuming a professional role. An overview of different aspects of the career intervention, that will be delivered through an e-learning platform, will be presented in this paper. Firstly, the theoretical support for the programme will be provided, including the Career Resources Model (Hirschi et al., 2017, 2018), the Self-Determination Theory (Ryan & Deci, 2017), Bloom's Taxonomy of Educational Objectives (Bloom, 2001; Krathwohl, 2002) and the virtual pedagogical model from Universidade Aberta (Pereira et al., 2007). Secondly, the needs identified in relation to career resources will be briefly displayed and it will be explained how they guided the programme’s construction. Career resources’ needs were identified through the Career Resources Questionnaire (Monteiro & Almeida, 2021, adapted from Hirschi et al., 2018), responded by graduates from two Portuguese universities, that surveyed the following career resources: occupational expertise, job market knowledge, soft skills, organizational career support, job challenge, social career support, career involvement, career confidence, career clarity, networking, career exploration, and continuous learning. Finally, the structure of the programme will be presented in conjunction with its goals and some specificities of the activities that will be proposed to students. What is planned for the assessment of the programme activities and the platform’s usability and accessibility, as well as for the evaluation of the intervention’s effectiveness is also included in this presentation. This programme is intended to be a socially and scientifically relevant contribution for academics, practitioners and policymakers, as well as for the graduates who will be enrolled in the programme, who, we expect, will engage in a set of activities suited to promote employability in efficient and effective ways. Given the flexibility concerning time and space of learning, this type of programme, supported by technologies, can contribute to student engagement, mainly among non-traditional publics, including workers, cultural minorities, or older students.